APPLICATIONS OF CERTAIN FUNCTIONS ASSOCIATED WITH LEMNISCATE BERNOULLI - Suzeini Abdul Halim; Rashidah Omar (Journal of the Indonesian Mathematical Society, 2012)
looked PDF abstractDOI : http://dx.doi.org/10.22342/jims.18.2.115.93-99